Single Layer Metamaterial Superstrate for Gain Enhancement of A Microstrip Antenna Array (Diyala Journal of Engineering Sciences, 2024)
This study focuses on creating and analyzing pentagonal microstrip patch antenna arrays with one, two, and three elements for use in the 10 GHz X-band range, utilizing a metamaterial (MTM) superstrate technique. The MTM superstrate, composed of open circular ring cells, is tailored for a 1×2 array with a 10×8 cell arrangement covering an area of 45×36 mm². A 1×3 array has a 14×12 cell configuration spanning 63×54 mm². Positioned beneath the radiating elements and optimized with a quarter-wave transformer for impedance matching, the superstrate significantly enhances antenna performance. The MTM superstrate alters the radiation pattern and increases the gain by approximately 2 dB, demonstrating a gain improvement of around 27% for high-gain applications in the X-band frequency range. For the 1×2 array, the gain increases from 7.52 dB to 9.58 dB, representing a 27.38% improvement, while the input reflection coefficient improves from -48.6 dB to -58.068 dB, reflecting a 19.5% enhancement. Similarly, for the 1×3 array, the gain rises from 9.69 dB to 11.6 dB, showing a 19.73% increase, and the input reflection coefficient improves from -57.46 dB to -60.64 dB, indicating a 5.54% improvement and a good radiation efficiency of about 79.11%. This work involves designing and simulating the proposed antenna arrays using the Computer Simulation Technology (CST) software.